Comparison between sodium–glucose cotransporter 2 inhibitors and pioglitazone as additions to insulin therapy in type 2 diabetes patients: A systematic review with an indirect comparison meta‐analysis - Cho, Yun Kyung; Kim, Ye‐Jee; Kang, Yu Mi; Lee, Seung Eun; Park, Joong‐Yeol; Lee, Woo Je; Jung, Chang Hee (Journal of diabetes investigation, 2018)
Aims/Introduction We aimed to evaluate the efficacy and safety of pioglitazone (PIO) and sodium–glucose cotransporter 2 inhibitors (SGLT2i) as additions to insulin therapy for the management of type 2 diabetes mellitus. Materials and Methods We searched PubMed, EMBASE, the Cochrane Central Register of Controlled Trials and ClinicalTrials.gov through December 2016. Randomized controlled trials published in English that compared SGLT2i plus insulin (SGLT2i/INS) or PIO plus insulin (PIO/INS) with placebo plus insulin (PCB/INS) in type 2 diabetes mellitus patients were included. We compared the efficacy and safety between SGLT2i/INS and PIO/INS indirectly. Results A total of 14 randomized controlled trials comparing 7,226 participants were included (8 SGLT2i and 6 PIO studies). SGLT2i/INS achieved similar reductions in hemoglobin A1c (weighted mean difference [WMD] −0.01% [−0.1 mmol/mol], 95% confidence interval [CI] −0.25 to 0.22% [−2.7 to −2.4 mmol/mol]; P = 0.896) and fasting plasma glucose (WMD −0.90 mg/dL, 95% CI: −15.50 to 13.71 mg/dL; P = 0.904), and a similar proportion of participants achieved hemoglobin A1c <7.0% (<53.0 mmol/mol; relative risk 0.98, 95% CI: 0.73 to 1.33; P = 0.917) as compared with the PIO/INS group, with greater weight reduction (WMD −4.54 kg, 95% CI: −5.67 to −3.41 kg; P < 0.001). PIO/INS showed non‐significant trends toward a higher risk of hypoglycemia (relative risk 1.15, 95% CI: 0.97 to 1.35; P = 0.102) and higher reduction of total daily insulin doses (WMD −2.45 IU/day, 95% CI: −7.30 to 2.40 IU/day; P = 0.438). Conclusions Both PIO and SGLT2i are feasible adjunctive oral agents to pre‐existing insulin therapy in individuals with inadequately controlled type 2 diabetes mellitus. Although the use of thiazolidinediones or SGLT2 inhibitors may be helpful in subjects with type 2 diabetes mellitus on insulin treatment, there has been no direct comparison of these two agents. In this indirect comparison meta‐analysis, both of pioglitazone and SGLT2 inhibitors showed comparable efficacy and safety.